Re-Visiting the Roadmaps to Low Carbon Economy - Sosu, Anita Esenam; Ahmed, Maruf Yakubu; Sarkodie, Samuel Asumadu (Springer, 2024)
While there is a growing demand for energy to sustain economic devel-opment, fossil fuels remain a threat to climate change. Yet, among all fossil fuels–– natural gas has low-carbon composition––which is crucial to achieving both energy security and decarbonized economic development. Here, we present the roadmaps to low-carbon economy and provide conceptual tools to navigate the paradigm of clean energy transition.
Keywords: carbon neutral economy; low-carbon economy; fossil fuel; energy consumption; green growth; natural gas; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|